An Overview of Attractive Marketing Content on Tiktok App Users - Nabila Athifa Wediana; Firosa Amalia Zain; Cindy Trisna Anggraini (International Conference on Psychology and Education (ICPE), 2023)
Content marketing is one of the media or marketing strategies to share content containing persuasive information about a product with consumers. The purpose of this study is to examine how marketing content is attractive to users of one of the most popular applications in use, namely Tiktok. This research was conducted using a qualitative approach, namely case studies and analyzed by thematic analysis to specifically identify patterns from the available data sets through the depiction of patterns from the content marketing phenomenon on Tiktok. Data collection was done by interview, observation, and FGD. The participants of this study were 10 people, with the criteria of having an interest in marketing content and making product purchases on Tiktok. From the results of data analysis, the authors found that users of the Tik Tok application had an interest in the marketing content presented. In an effort to improve marketing strategy, producers need to pay attention to supporting factors such as presenting attractive marketing content by paying attention to the aspect of observing marketing content, contributing factors, and decision making by consumers.